IgLON5 deficiency produces behavioral alterations in a knockout mouse model - Landa, Jon; Serafim, Ana Beatriz; Alba, Mercedes; Maudes, Estibaliz; Molina-Porcel, Laura; Garcia-Serra, Anna; Mannara, Francesco; Dalmau, Josep; Graus, Francesc; Sabater, Lidia (Frontiers in Immunology, 2024)
Background: Anti-IgLON5 disease is a neurological disorder characterized by autoantibodies against IgLON5, and pathological evidence of neurodegeneration. IgLON5 is a cell adhesion molecule of unknown function that is highly expressed in brain. Our aim was to investigate the impact of IgLON5 loss-of-function evaluating the brain morphology, social behavior, and the development of symptoms observed in an IgLON5 knockout (IgLON5-KO) mouse model.The IgLON5-KO mouse was obtained with CRISPR-Cas9 technology. Immunohistochemistry on fixed sagittal brain sections and western blot brain lysates were used to confirm IgLON5 silencing and to evaluate the presence of other cell surface proteins. Two-month old IgLON5-KO and wildtype (WT) mice underwent a comprehensive battery of behavioral tests to asses: 1) locomotion; 2) memory; 3) anxiety; 4) social interaction and 5) depressive-like behavior. Brain sections were examined for the presence of anatomical abnormalities and deposits of hyperphosphorylated tau in young adults (2-month old) and aged (22-month old) mice.Results: Mice did not develop neurological symptoms reminiscent of those seen in patients with anti-IgLON5 disease. Behavioral testing revealed that 2-month old IgLON5-KO mice showed subtle alterations in motor coordination and balance. IgLON5-KO females exhibit hyperactivity during night and day and in males, we observed a depressive-like behavior and, excessive nest building behavior. Neuropathological studies did not reveal brain morphological alterations or hyperphophorylated tau deposits.Conclusions: IgLON5-KO mice show subtle alterations in behavior and deficits in fine motor coordination but do not develop the clinical phenotype of anti-IgLON5 disease.